Tender Rigging in the Procurement of Cryo-Electron Microscopes (Cryo-EM) and Transmission Electron Microscopes (TEM) at BRIN (Case Study Decision: 02/KPPU-L/2024) - Ardiana, Oktavia Dwi; Hutabarat, Sylvana Murni Deborah (Jurnal Daulat Hukum, 2025)
This study discusses the practice of tender rigging in the procurement of Cryo-Electron Microscope (Cryo-EM) and Transmission Electron Microscope (TEM) at BRIN based on Case Decision Number 02/KPPU-L/2024. The purpose of this study is to analyze the form of tender rigging violations that violate the provisions of Article 22 of Law No. 5 of 1999 and examine its impact on business competition, business actors, the state, and research development in Indonesia. The research method used is normative juridical with a statute approach and a case approach with qualitative data analysis methods. The results of the study indicate the existence of vertical collusion between the tender committee, namely the Working Group and the PPK with business actors, namely PT Buana Prima Raya as the tender winner and PT Multi Teknindo Infotronika as the sole agent for the product. The tender rigging was characterized by the arrangement of technical specifications that favored certain brands, discrimination by unilaterally withdrawing support from PT Transformasi Sejahtera Indonesia as the lowest bidder, and the increase in procurement and contract prices without going through a transparent competition mechanism. The resulting impacts included the creation of artificial competition, state financial losses, hampered innovation in the research sector, and a decline in national competitiveness in mastering high technology. This research emphasizes the need for strict oversight and a fair resolution mechanism so that the tender system in Indonesia can operate transparently and accountably.